Evaluation of tests performed to confirm the position of the Veress needle for creation of pneumoperitoneum in selected patients: a prospective clinical trial - Azevedo, Otávio Cansanção [UNIFESP] (2006)
PURPOSE: To evaluate tests performed to confirm the position of the Veress needle inserted into the left hypochondrium for creation of pneumoperitonium. METHODS: One hundred patients were submitted to laparoscopic procedure with left hypochondrium puncturing. Needle positioning tests were evaluated. The aspiration test was considered positive when organic material was aspirated; the injection test was considered positive when no increased resistance to liquid injection was observed; the recovery test was considered positive when the liquid injected was not recovered; the saline drop test was considered positive when drops of saline in the syringe disappeared quickly; the initial intraperitoneal pressure test was considered positive when pressure levels were £ 8 mmHg. A positive aspiration test indicated iatrogenic injury, whereas a positive result in any of the other tests indicated that the tip of the needle was correctly positioned in the peritoneal cavity. Sensitivity (SE), specificity (SP), positive predictive value (PPV) and negative predictive value (NPV) of the tests were calculated by correlating results considered true positives (a), false positives (b), false negatives (c) and true negatives (d), according to the formulas: SE = [a/(a + c)] x 100; SP = [d/(b + d)] x 100; PPV = [a/(a + b)] x 100; NPV = [d(c + d)] x 100. RESULTS: With regard to the aspiration test, SE and PPV were not applicable, SP was 100% and NPV was 100%. With regard to the injection test, SE was 0%, SP was 100%, PPV was inexistent and NPV was 90%. Both recovery and saline drop tests yielded the following results: SE was 50%, SP was 100%, PPV was 100% and NPV was 94.7%. The initial intraperitoneal pressure test yielded the following results: SE, SP, PPV and NPV were 100%. CONCLUSIONS: When inserting the Veress needle into the left hypochondrium, a negative aspiration test guarantees the absence of iatrogenic injury; the injection test is not reliable to determine incorrect needle positioning, but it accurately detects correct needle positioning; recovery and saline drop tests are not reliable to determine correct needle positioning, but they accurately detect incorrect needle positioning; the initial intraperitoneal pressure test is reliable to determine both correct and incorrect needle positioning, and proved to be the most reliable of the tests analyzed.